A novel End-effector Finger Rehabilitation Robot (EFRR) for stroke patients. Issue 5 (April 2021) - Hongbo, Wang; Yu, Tian; Baoshan, Niu; Jiazheng, Du; Junjie, Tian
Abstract: This paper proposes a prototype of a novel end-traction finger rehabilitation robot with flexion/extension and adduction/abduction functions. The degree of freedom (DoF) and finger joint torque of a single-finger module has been analysed, and the calculation and selection of the motor driving force are completed. Finally, the design details of the mechanism and the hardware system of the robot are illustrated. This device minimized the mechanical size to some extent by using only one motor for a single finger, which also reduces the cost and increases the possibility of industrial application prospects.